Między folwarkiem a szybem Ziemianie galicyjscy a nafta na przykładzie Jasła i powiatu jasielskiego - Laskowski, Andrzej (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2010)
Surroundings of Jasło – provincial town situated in a half way between two political and cultural centers of Galicia: Kraków and Lwów – become in the fifties of the 19th century the cradle of oil industry. The first oil mine and – above all – the first industrial oil distiller in the world started to work just very close to it. Together with a growth of oil mining in the region Jasło itself become before 1900 an unofficial capital of Galician oil industry. A prosperity of the town was very close connected to rock oil exploration executed by the owners of the grounds situated in the neighborhood, in fact most of all the local gentry. Its traditional way of economic existence, based on the agriculture, had to be faced with a brand new way of thinking, characteristic for the industrial development. In this confrontation a local gentry appeared a class brave enough to be strongly engaged into the industrial process and – in the same way – very faithful (but not conservative) in its attitude to farming. Even the most successful noblemen in the field of oil industry did not give up with it and still treated it as a field of fruitful competition between each other.